Forest management for eco-tourism: understanding the community perspective of co-management - Zainah Othman,; Ahmad Fariz Mohamed,; Abdul Samad Hadi,; Shaharuddin Ismail, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
Forest management for eco-tourism needs to emphasis on the participation of the community to ensure that eco-tourism products remain sustainable. Without active involvement by the community, eco-tourism products face the risk of being destroyed by the ravages of overzealous economic development activities. Of paramount importance is the need for a balance of economic development and sustainable forest management. The forest inhabitants and the community need to be in symbiotic relations in order to survive in the forest. This study seeks to understand the community perspectives in co-managing the eco-tourism forest in RBFRSP. For that reason, three community representatives, including two Penghulu and a Tok Batin were interviewed to seek their perspectives on co-management. The results, in a nutshell, indicate that the community is not ready for co-management.